2020
DOI: 10.3389/fcvm.2020.586491
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Strategy for Antiplatelet Therapy After Coronary Drug-Eluting Stent Implantation in High-Risk “TWILIGHT-like” Patients With Diabetes Mellitus

Abstract: Background: Patients with diabetes mellitus (DM) are known to be at high-risk for both ischemic and bleeding complications post-percutaneous coronary intervention (PCI). The ischemic benefit vs. bleeding risk associated with extended dual antiplatelet therapy (DAPT) in high-risk “TWILIGHT-like” patients with diabetes mellitus after PCI has not been established.Methods: All consecutive high-risk patients fulfilling the “TWILIGHT-like” criteria undergoing PCI from January 2013 through December 2013 were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…The inconsistent results and lower incidence of bleeding and ischemic events might contribute to a high proportion of bleeding and ischemic events, which might contribute to a high proportion of the trial population treated with prasugrel, ethnic differences, procedural improvements, and changes in bleeding avoidance strategies over time. Nevertheless, the incidence of ischemic and bleeding events in the present study was similar to that observed between 1 and 2 years after PCI in other trials involving East Asian populations (18,19). Considering the contemporary clinical practice, extended P2Y12 inhibitor monotherapy with clopidogrel might be an optimal antiplatelet strategy.…”
Section: Discussionsupporting
confidence: 88%
“…The inconsistent results and lower incidence of bleeding and ischemic events might contribute to a high proportion of bleeding and ischemic events, which might contribute to a high proportion of the trial population treated with prasugrel, ethnic differences, procedural improvements, and changes in bleeding avoidance strategies over time. Nevertheless, the incidence of ischemic and bleeding events in the present study was similar to that observed between 1 and 2 years after PCI in other trials involving East Asian populations (18,19). Considering the contemporary clinical practice, extended P2Y12 inhibitor monotherapy with clopidogrel might be an optimal antiplatelet strategy.…”
Section: Discussionsupporting
confidence: 88%
“…Covariates used for the propensity score model included age, sex, body mass index, current smoker, diabetes, hypertension, dyslipidemia, previous MI, previous PCI, previous stroke, peripheral vascular disease, chronic obstructive pulmonary disease, total cholesterol, LDL-C, total lesion length, type B2 or C lesion, chronic total occlusion (CTO), bifurcation lesion, number of lesions treated, stent number, use of everolimus-or zotarolimus-eluting stent, and use of aspirin, P2Y 12 inhibitor, β-blocker, and statin at discharge. The detailed methods of IPTW analysis were previously described (26).…”
Section: Discussionmentioning
confidence: 99%
“…This was an analysis of a single center, prospective study, and the study design has been previously described. 17 , 18 Patients with stable CAD who underwent PCI with DES implantation at Fuwai Hospital, National Center for Cardiovascular Diseases, between January 2013 and December 2013 were selected. Stable CAD refers to patients with CAD who are clinically stable (ie, who are not in an unstable phase such as an acute coronary syndrome [ACS]).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed methods of IPTW analysis were previously described. 18 All statistical analyses were conducted with SPSS version 23.0 (IBM, Armonk, NY) and R version 3.6.0 (R Foundation for Statistical Computing, Vienna, Austria). A 2‐sided P value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%